Kesiapan mahasiswa pendidikan matematika dalam praktik pengalaman lapangan di sekolah - Aminullah Aminullah; Rusgianto Heri Santosa (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2018)
Penelitian ini bertujuan untuk mendeskripsikan kesiapan mahasiswa pendidikan matematika se-Kota Mataram dalam melaksanakan Praktik Pengalaman Lapangan (PPL) di sekolah yang ditinjau dari: kesiapan kompetensi pedagogi mahasiswa dan kesiapan kompetensi kepribadian mahasiswa. Penelitian ini menggunakan pendekatan concurrent embedded strategy of mixed method. Sampel penelitian terdiri atas 104 mahasiswa pendidikan matematika yang melaksanakan PPL di sekolah, yang ditentukan menggunakan teknik purposive sampling. Instrumen penelitian berupa tes, daftar ceklis, lembar observasi, dan angket. Analisis data menggunakan analisis statistik deskriptif kuantitatif dengan kecenderungan kesiapan dalam lima kategori yaitu sangat siap, siap, cukup, kurang, dan sangat kurang. Hasil penelitian menunjukkan bahwa (1) kompetensi pedagogi mahasiswa masuk kategori cukup, (2) wawasan kompetensi pedagogi masuk kategori siap, (3) kemampuan menyusun RPP masuk kategori siap, (4) kemampuan melaksanakan pembelajaran masih kurang, (5) kemampuan menilai hasil belajar masuk kategori cukup, dan (6) kompetensi kepribadian mahasiswa masuk kategori cukup. The readiness of mathematics education students in mataram city in the teaching practicum at schools AbstractThis study aimed to describe the readiness of mathematics education students in Mataram City in implement the teaching practicum at schools in terms of the pedagogic competence and the personal competence. This study using the approach of the concurrent embedded strategy of mixed methods. The study sample consisted of 104 mathematics education students who carried out the teaching practicum at schools, which was determined using purposive sampling technique. The study instruments consist of a test, checklists, observation sheets, and questionnaires. The data were analyzed by means of the descriptive statistics using readiness tendencies in five categories: very ready, ready, fairly ready, poor, and very poor. The results of the study show that (1) the pedagogical competence of students was in the fairly ready category, (2) the pedagogic competence knowledge was in the ready category, (3) the ability to design lesson plans was in the ready category, (4) the ability to implement teaching was in the poor category, (5) the ability to assess students’ learning achievements was in the fairly ready category, and (6) the personal competence was in the fairly ready category.